Absence of cytomegalovirus in gingivitis and chronic periodontitis in HIV-1 patients in Northern Brazil - Ricardo Roberto de Souza Fonseca; Ana Cláudia Braga Amoras Alves; Thalita de Almeida Amanajás; Brenna Magdalena Lima Nogueira; Tatiany Oliveira de Alencar Menezes; Leonardo Quintão Siravenha; Danilo Leôncio Aguiar Pereira; Luiz Fernando Almeida Machado; Luciana Campêlo da Silva Gilet; Silvio Augusto Fernandes de Menezes (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION The influence of cytomegalovirus (CMV) on the progression of chronic periodontitis in HIV patients is poorly investigated. METHODS ELISA was used for anti-CMV antibody IgG titer measurements and real-time polymerase chain reaction for qualitative and quantitative CMV detection. Data on the CD4 + T lymphocyte count and plasma HIV viral load were obtained from patient records. RESULTS CMV DNA was detected in samples of subgingival biofilm in only three individuals, two of them with chronic periodontitis (4%) and one with gingivitis (3.3%). CONCLUSIONS The prevalence of CMV is very low both in HIV-1 patients with gingivitis and chronic periodontitis.